Elevation of Interleukin-18 Correlates With Cardiovascular, Cerebrovascular, and Peripheral Vascular Events: A Cohort Study of Hemodialysis Patients. Issue 42 (October 2015) - Chang, Chih-Hsiang; Fan, Pei-Chun; Lin, Chan-Yu; Yang, Chia-Hung; Chen, Yi-Ting; Chang, Su-Wei; Yang, Huang-Yu; Jenq, Chang-Chyi; Hung, Cheng-Chieh; Yang, Chih-Wei; Chen, Yung-Chang
Abstract : Abstract: Cardiocerebral vascular events are the major cause of mortality among patients with end-stage renal disease (ESRD). Subclinical inflammation and atherosclerosis have been implicated in the pathophysiology of ESRD. Evidence has shown the crucial role of interleukin-18 (IL-18) in inflammation. Interleukin-18 has been markedly upregulated in ESRD patients. Nevertheless, the ability of the IL-18 level to predict cardiocerebral vascular events and the correlation between IL-18 levels and cardiocerebral vascular events have not been established in hemodialysis patients. To determine whether the serum IL-18 level predicts cardiocerebral vascular events, the authors studied 171 ESRD patients. Samples were collected and patients were followed for 24 months. Demographic data, the duration of hemodialysis, nutrition status, inflammatory parameters, dialysis adequacy, and lipid profiles were analyzed to predict the outcome by using multivariate logistic regression. Cutoff points were calculated by acquiring the highest Youden index. The Kaplan–Meier method was used to scrutinize the cumulative proportion of events. The multivariate logistic regression model revealed that serum creatinine, C-reactive protein, and IL-18 levels were independent predictors for cardiocerebral vascular events. The odds ratio of events for each increase in IL-18 (pg/mL) was 1.008 for cardiocerebral vascular events. The area under the receiver operating characteristic curve of IL-18 was 0.779 ± 0.039, the overall correctness was 73%, and the Youden index was highest at a cutoff of 463 pg/mL. In the Kaplan–Meier model, patients with an IL-18 level higher than 463 pg/mL exhibited the highest probability of experiencing an adverse event during the entire follow-up period. Increased serum IL-18 could be considered as a predictor of cardiocerebral vascular events in dialysis patients. It is noteworthy that various comorbidities might interfere the expression of IL-18; therefore, further validation study is required to incorporate IL-18 in clinical use.